Improving Rebalanced RSA Against Chosen Ciphertext Attacks - Padmaja, Ch J.L; Bhagavan, V.S; Srinivas, B (International Journal of Computer Sciences and Engineering, 2025)
RSA cryptosystem is the most widely used public key cryptosystem. There have been many variants to the original RSA proposed in the literature and Rebalanced RSA is one of such modified RSA cryptosystems. This paper provides new designs of Rebalanced RSA which are semantically secure against chosen ciphertext attack as well as adaptive chosen ciphertext attack. The proposed schemes are proved to be more efficient than other schemes like DRSA, Rebalanced RSA and standard RSA.